2017
DOI: 10.1186/s12862-017-0912-4
|View full text |Cite
|
Sign up to set email alerts
|

Eco-evolution in size-structured ecosystems: simulation case study of rapid morphological changes in alewife

Abstract: BackgroundOver the last 300 years, interactions between alewives and zooplankton communities in several lakes in the U.S. have caused the alewives’ morphology to transition rapidly from anadromous to landlocked. Lakes with landlocked alewives contain smaller-bodied zooplankton than those without alewives. Landlocked adult alewives display smaller body sizes, narrower gapes, smaller inter-gill-raker spacings, reach maturity at an earlier age, and are less fecund than anadromous alewives. Additionally, landlocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Trophic interactions may contribute to the resource context within which functional traits related to resource acquisition may evolve (Kang & Thibert-Plante, 2017). On a macroevolutionary timescale, intra-and inter-specific competition for resources can drive speciation (Gavrilets et al, 2007;Weber et al, 2017).…”
Section: How To Model Eco -E Volutionary Feedback Loops: From Analy T...mentioning
confidence: 99%
See 3 more Smart Citations
“…Trophic interactions may contribute to the resource context within which functional traits related to resource acquisition may evolve (Kang & Thibert-Plante, 2017). On a macroevolutionary timescale, intra-and inter-specific competition for resources can drive speciation (Gavrilets et al, 2007;Weber et al, 2017).…”
Section: How To Model Eco -E Volutionary Feedback Loops: From Analy T...mentioning
confidence: 99%
“…Most of the reviewed multispecies DG‐ABMs focussed on competitive interactions, in an explicit prey–predators' or community context. For instance, Kang and Thibert‐Plante (2017) illustrated that considering trophic interactions and the genetic basis of functional traits within a single model could improve the understanding of evolutionary morphological changes in fish. Hillaert et al (2020) showed that in a fragmented habitat, the presence of predators selects for increased herbivore movement and hence larger herbivore size.…”
Section: Extending In Space Time and Levels Of Organizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding patterns of resource use provides insight into the evolution and maintenance of the intraspecific phenotypic diversity observed within many aquatic taxa (Hawley et al, 2016;Kang and Thibert-Plante, 2017;Kane et al, 2022). Differential resource use can limit intraspecific competition across life stages as well as buffer against extinction risk by spatially segregating a population into different habitats (Schindler et al, 2015;Østbye et al, 2020).…”
Section: Introductionmentioning
confidence: 99%